Health Care Providers’ Perceptions of the Ministry of Health’s Organizational Readiness for Change - Jamilah Almuqati; Mysara Alfaki; Ahmed Alkarani (Nurse Media: Journal of Nursing, 2023)
Background: Whenever an organisational change is mentioned in any research context, the uncertainty concept is usually mentioned as it is or as synonymous with lack of information, ineffective communication, and/or weak feedback. Since no previous studies have investigated the organisation’s readiness to change in Saudi Arabia, this study will provide empirical evidence regarding these critical components.